2021
DOI: 10.25259/sni_100_2021
|View full text |Cite
|
Sign up to set email alerts
|

Early chemoprophylaxis for deep venous thrombosis does not increase the risk of hematoma expansion in patients presenting with spontaneous intracerebral hemorrhage

Abstract: Background: Spontaneous intracerebral hemorrhage (ICH) is a significant cause of morbidity and mortality worldwide. The development of venous thromboembolism (VTE), including deep venous thrombosis or pulmonary embolism, is correlated with negative outcomes following ICH. Due to the risk of hematoma expansion associated with the use of VTE chemoprophylaxis, there remains significant debate about the optimal timing for its initiation following ICH. We analyzed the risk of early chemoprophylaxis on hematoma exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
(24 reference statements)
1
1
0
Order By: Relevance
“…9 Based on the difference in study design, 7 cohort studies mainly compared the application of prophylactic anticoagulation therapy with no anticoagulation therapy, 27 prophylactic anticoagulation therapy combined with GCS versus GCS alone, 28 and anticoagulation therapy early (eg, within 24 h) and late (eg, day 10). 26,32,33,35,36 The results of the above studies are consistent with the finding that the incidence of HE in patients with ICH who received pharmacological prophylaxis is similar to that in the control group, even when applied within 24 hours of ICH onset. The same safety (in terms of HE) of direct oral anticoagulants after ICH has also been reported.…”
Section: Safety Of Pharmacological Prophylaxissupporting
confidence: 85%
See 1 more Smart Citation
“…9 Based on the difference in study design, 7 cohort studies mainly compared the application of prophylactic anticoagulation therapy with no anticoagulation therapy, 27 prophylactic anticoagulation therapy combined with GCS versus GCS alone, 28 and anticoagulation therapy early (eg, within 24 h) and late (eg, day 10). 26,32,33,35,36 The results of the above studies are consistent with the finding that the incidence of HE in patients with ICH who received pharmacological prophylaxis is similar to that in the control group, even when applied within 24 hours of ICH onset. The same safety (in terms of HE) of direct oral anticoagulants after ICH has also been reported.…”
Section: Safety Of Pharmacological Prophylaxissupporting
confidence: 85%
“…It is worth mentioning that most of these studies found no significant difference in the incidence of VTE between the compared groups. [26][27][28][29]32,34,36,37 This is probably due to the limited number of RCTs and reduced sample size of studies. To better overcome this difficulty, several meta-analyses have been reported.…”
Section: Efficacy Of Pharmacological Prophylaxismentioning
confidence: 99%